2021
DOI: 10.1029/2021gl094000
|View full text |Cite
|
Sign up to set email alerts
|

Are Multiseasonal Forecasts of Atmospheric Rivers Possible?

Abstract: Atmospheric rivers (ARs)-corridors of intense moisture flux with transport intensity of over 180,000 tons of moisture per second-are uniquely characterized by plume-like features with a length over 1,000 km and a width about one-third of its length (Newell et al., 1992;Ralph et al., 2018;Zhu & Newell, 1998). AR intensity and duration span a wide range and sometimes can lead to different socio-economic impacts. Previous work has categorized ARs into five categories according to certain intensity and duration cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
(57 reference statements)
0
12
0
Order By: Relevance
“…Previous research has examined ARs in SPEAR and AM4 showing its capability of reproducing the observed climatology, including frequency, numbers and geometry (Zhao, 2020). In addition, SPEAR also shows the capability of forecasting multiseasonal AR activity and capturing interannual variability in the present climate (Tseng et al., 2021), which gives us additional confidence for projecting future AR activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has examined ARs in SPEAR and AM4 showing its capability of reproducing the observed climatology, including frequency, numbers and geometry (Zhao, 2020). In addition, SPEAR also shows the capability of forecasting multiseasonal AR activity and capturing interannual variability in the present climate (Tseng et al., 2021), which gives us additional confidence for projecting future AR activity.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, SPEAR also shows the capability of forecasting multiseasonal AR activity and capturing interannual variability in the present climate (Tseng et al, 2021), which gives us additional confidence for projecting future AR activity.…”
Section: Global Climate Model Large Ensemblementioning
confidence: 99%
“…ARs are typically associated with a low-level jet stream ahead of the cold front of an extratropical cyclone, and frequently lead to heavy precipitation when they are forced upward by mountains or frontal lift 9,10 . Along the west coast of North America (NA), high-impact ARs often arrive in the cold season when weather is dominated by the strong onshore flow of Pacific airstreams 2,9,[11][12][13][14] . Some of these systems are also known as pineapple express storms for their apparent origin in the tropical area near Hawaii [15][16][17] .…”
mentioning
confidence: 99%
“…The focus of this study is on the December-January-February (DJF) season from SRF initialized on 1 st December. SPEAR's SRF has shown significant seasonal forecast skill in predicting a wide range of essential indicators of climate variability, including but not limited to the SST, SAT over land, mid-latitude baroclinic waves, Antarctic/Arctic sea ice, Kuroshio extension, North American summertime heat extremes, and atmospheric rivers over Western North America (Lu et al, 2020;Bushuk et al, 2021Bushuk et al, , 2022Tseng et al, 2021;Zhang et al, 2021;Jia et al, 2022;Joh et al, 2022).…”
Section: Methodsmentioning
confidence: 99%